Effect of Shape on Strength and Durability of Crushed and Uncrushed Quartzite Aggregates from Central Nepal Himalaya - Sharma, Dinesh Raj; Tamrakar, Naresh Kazi (Malaysian Journal of Science (MJS), 2025)
This study examines the influence of shape on the strength and durability of angular (crushed) and rounded (uncrushed) quartzite aggregates sourced from the Central Nepal Himalaya. Crushed quartzite samples, characterized by angular morphologies, exhibit enhanced interlocking and greater variability in mechanical properties such as Point Load Strength Index (PLSI), Aggregate Impact Value (AIV), and Aggregate Crushing Value (ACV), due to their rough textures. In contrast, rounded (uncrushed) quartzite from alluvial gravels, with subrounded particles, demonstrates more consistent strength and durability, as evidenced by narrower ranges in PLSI, AIV, and ACV. Durability tests, including Slake Durability Index (SDI), Los Angeles Abrasion Value (LAAV), and Sulfate Soundness Value (SSV), indicate that angular aggregates provide superior abrasion resistance, whereas subrounded aggregates display more uniform resistance to sulfate-induced weathering. These findings offer valuable insights for selecting quartzite aggregates based on shape to optimize performance in construction applications.